Improvement in the renal prognosis in nephropathic cystinosis - Stralen, Karlijn J. van; Emma, Francesco; Jager, Kitty J.; Verrina, Enrico; Schaefer, Franz; Laube, Guido F.; Lewis, Malcolm A.; Levtchenko, Elena N. (Clinical journal of the American Society of Nephrology, 2011)
Background and objectives Nephropathic cystinosis (NC) is an autosomal recessive disorder occurring in one to two per 100,000 newborns. Because of the rarity of NC, long-term outcome data are scarce. Design, setting, participants, & measurements 245 NC patients from 18 countries provided data to the ESPN/ERA-EDTA registry. We matched NC patients on renal replacement therapy (RRT) to non-NC children on RRT. Results Between 1979 and 2008, mean age at the start of RRT among NC children increased by 0.15 year per calendar year (95% confidence interval, 0.10 to 0.21) from 8.8 to 12.7 years, whereas we did not observe this in non-NC children. Five-year survival after the start of RRT improved in NC patients from 86.1% (before 1990) to 100% (since 2000) as compared with the control population (89.6% and 94.0%). NC patients received a renal allograft more often (relative risk, 1.09; 95% confidence interval, 1.00 to 1.17) as compared with matched RRT children, and 5-year graft survival was better (94.0% versus 84.0%). NC dialysis patients were less often hypertensive than non-NC children matched for age, country, and dialysis modality (42.7% versus 51.7%) and had lower parathyroid hormone levels (median, 56 versus 140 pg/ml). Although height at start of RRT slightly improved during the past decade, children with NC remained significantly shorter than non-NC children at the start of RRT. Conclusions We demonstrated improved survival of the renal function as well as better patient and graft survival after the start of RRT in a large European cohort of NC patients over the last two decades.
Gesehen am 07.12.2022